Unveiling coastal diversity: An inventory and conservation report of beach forest flora of Surigao del Sur, Philippines - GISELLE B. RAMOS; JOCELYN B. PANDUYOS; ROXAN E. CARAY; LUZMINDA S. BACQUIAL (Society for Indonesian Biodiversity, 2024)
Abstract. Ramos GB, Panduyos JB, Caray RE, Bacquial LS. 2024. Unveiling coastal diversity: An inventory and conservation report of beach forest flora of Surigao del Sur, Philippines. Biodiversitas 25: 421-430. Coastal greenbelts, comprise mangroves and beach forest trees, are pivotal in disaster mitigation and climate change resilience. Despite the evident importance of these coastal ecosystems, they are often overlooked in research due to a lack of comprehensive data on species community structure and their broader ecological importance. Hence, this present study was conducted to document beach forests composition and conservation status in selected coastal municipalities of Surigao del Sur, Philippines. The study was conducted in five sampling locations, namely, La Paz, Bil-at, Balibadon, Poblacion Cagwait and Arangasa Island. At each sampling location, a 2 km transect line, parallel to the beach’s shoreline, was established having a 100 square meter sampling plots spaced 50m apart. Beach species frequency counts, percentages, and diversity indices were quantified. The study documented 27 beach forest species belonging to 21 families and 25 genera with the dominant species being Crinum asiaticum, Cocos nucifera, Millettia pinnata, Timonius compressicaulis, and Terminalia catappa. Both Arangasa Island and La Paz beach forests have the highest species diversity (H’ = 2.04); however, Cagwait has the highest species richness (Margalef = 2.34). This study has potential to significantly contribute in addressing existing data gap regarding beach forest species in the Philippines. With the looming threat of extinction due to infrastructural development and anthropogenic activities, the study's outcomes stand as an urgent call to action; thus, a collaborative endeavor of Local Government Units, academicians, and community for conservation and protection before these species succumb to the threat of extinction.